Study of Testing Method for Dynamic Initiation Toughness of Sandstone under Blasting Loading - Dingjun Xiao; Zheming Zhu; Rong Hu; Lin Lang (Shock and Vibration)
In this paper, an internal central single-cracked disk (ICSCD) specimen was proposed for the study of dynamic fracture initiation toughness of sandstone under blasting loading. The ICSCD specimen had a diameter of 400 mm sandstone disc with a 60 mm long crack. Blasting tests were conducted by using the ICSCD specimens. The blasting strain-time curve was obtained from the radial strain gauges placed around the blast hole. The fracture initiation time was determined by circumferential strain gauges placed around the crack tip. The stress history on the blast hole of the sandstone specimen was then derived from measured strain curve through the Laplace transform. The numerical solutions were further obtained by the numerical inversion method. A numerical model was established using the finite element software ANSYS. The type I dynamic stress intensity factor curves of sandstone under blasting loading were derived by the mutual interaction integration method. The results showed that (1) the ICSCD specimen can be used to measure dynamic initiation fracture toughness of rocks; (2) the stress on the blast hole wall can be obtained by the Laplace numerical inversion method; (3) the dynamic initiation fracture toughness of the ICSCD sandstone specimen can be calculated by the experimental-numerical method with a maximum error of only 7%.